Vulnerability of NCDs and Mediating Effect of Risk Behaviors Among Tuberculosis Patients and Their Household Contacts Compared to the General Population in the Yangon Region, Myanmar - Zayar NN; Chotipanvithayakul R; Bjertness E; Htet AS; Geater AF; Chongsuvivatwong V (International Journal of General Medicine, 2023)
Nyi Nyi Zayar,1 Rassamee Chotipanvithayakul,1 Espen Bjertness,2 Aung Soe Htet,2 Alan Frederick Geater,1 Virasakdi Chongsuvivatwong1 1Department of Epidemiology, Faculty of Medicine, Prince of Songkla University, Hat Yai, Songkhla, 90110, Thailand; 2Department of Community Medicine and Global Health, Institute of Health and Society, Faculty of Medicine, University of Oslo, Oslo, NorwayCorrespondence: Rassamee Chotipanvithayakul, Department of Epidemiology, Faculty of Medicine, Prince of Songkla University, 6th Floor of Administrative Building, 15 Kanjanavanich Road, Hat Yai, Songkhla, 90110, Thailand, Tel +66-074-451165, Email rassamee.s@psu.ac.thPurpose: We investigated the association of TB patients and their household contacts with diabetes mellitus (DM) and hypertension compared to the general population, and the mediating effects of risk behaviors including current smoking, alcohol drinking, and poor diet quality.Patients and Methods: A cross-sectional study on screening for DM, hypertension, and risk behaviors among newly diagnosed TB patients (n = 221) and their household contacts (n = 257) aged 25– 74 years in Yangon in 2018. Health data of the general population (n = 755) were obtained from an NCD risk factor survey in Yangon. A directed acyclic graph is used to identify possible pathways of association between variables. Associations are presented as adjusted odds ratios (aOR).Results: Compared to the general population, both TB patients and their household contacts were associated with current smoking and drinking, and TB patients were more likely to be underweight. Without considering mediating effects, TB patients had higher odds of DM (aOR = 6.3, 95% CI: 3.8– 10.6), but both TB patients and household contacts had lower odds of hypertension (aOR = 0.54; 95% CI: 0.33– 0.87) and (aOR = 0.68; 95% CI: 0.47– 0.98), respectively. The body mass index-mediated pathway reduced the odds of DM and hypertension among TB patients (aOR = 3.4; 95% CI: 2.2– 5.3) and (aOR = 0.3; 95% CI: 0.2– 0.5), respectively.Conclusion: The shared risk behaviors among TB patients and household contacts with high burden of DM in TB patients endorse screening of risk behaviors and strengthening the integration of NCD services among TB patients and household contacts in this dual-burden country.Keywords: TB, diabetes mellitus, hypertension, non-communicable diseases, screening, mediator